(3CSGSjGJ Yde GdGbJUGO (B:s (3eONd dOQGSI CUhd GdGbJUGO GdSjGSj (B/s - (3YhV Gddg, RjfH MSjfs; (3MTjT, YGOd CMeO s ((3GdGScfOQjI(B: s (3OGQ GdLGeI GdLOjOI(B, s, 2006)
(3eaghe GdeTcdI GdGbJUGOjI ddeLJeYGJ GdGfSGfjI (B( (3JMdjd dYhGed fTCJgG h WHjYI GdMGLGJ h GdehGQO GdeJbGHdI aj fWGbgG (B)(3, ebheGJ Md GdeTcdI GdGbJUGOjI h GdWHjYI GdGLJeGYjI dYedjI GdMd HeQGYGI GdJCKjQGJ GdfGJLI Yf GdfXe GdGbJUGOjI GdSGFOI h GdfWGb GdehVhYj ddGbJUGO GdSjGSj h GfHKGb GdehVhYGJ GdTGZdI dGgJeGeGJ GdGbJUGOjjf ef YfGUQ GdeTcdI GdGbJUGOjI , GdWHjYI GdeROhLI ddOQGSI aj eLGd GdGbJUGO GdSjGSj h eOi GSJMbGbg ddebheGJ GdGSGSjI aj hUa GdYde , YfGUQ GdGfJGL GdeJWdHI dbjGe GdeTQhY GdGbJUGOj HGfJGL GdSdY h GdNOeGJ GdGfJGLjI h GdGSJgdGcjI h HMK bhGfjf GdZdI h GdfabI PGJ GdYdGbI HGdGhLg GdafjI ddGfJGL HGYJHGQ GdYedjGJ GdGfJGLjI bVjI GbJUGOjI h afjI , GdWdH h GdYQV ceJZjQjf GbJUGOjjf QFjSjjf h JCKjQ GdbhGfjf GdGbJUGOjI GdMGceI dgeG Ydi bQGQGJ h JUQaGJ GdeSJgdcjf h GdefJLjf , GdShb GdQCSeGdj h GdJNWjW GdGTJQGcj h cjajI JMOjO CKeGf GdefJLGJ aj GdfeGPL GdeJYGQa YdjgG ddCShGb GdQCSeGdjI (B( (3GdGKeGf ceMOO dSjGSI GdeTQhY GdGfJGLjI h cjajI JMOjO CKeGf NOeGJ YfGUQ GdGfJGL habG ddBdjGJ GdeJYGQa YdjgG HGdGShGb ,GdGKeGf h OhQgG aj GdGgJOGA deDTQGJ ehVhYjI Jcad SdGeI JNUU GdehGQO GdGbJUGOjI ajeG Hjf ChLg GdGfJGL h GdJhRjY h GdGSJgdGc aj GdfXGe GdGbJUGOj ddGTJQGcjI h CNjQG GdGbJUGO GdSjGSj h eYGde GdJWhQGJ h GdJMhdGJ GdeSJLOI Ydi SGMI GdfXe h GdJfXjeGJ GdGbJUGOjI GdeJYdbI HGdGSJeQGQ GdGbJUGOj ddeLJeYGJ GdeYGUQI (B.s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdSjGSjs; (3GdeTcdGJ GdEbJUGOjIs; (3Yde GdEbJUGOs